Femoral vs. radial approach for primary percutaneous intervention in cardiogenic shock: a subanalysis from the ECLS-SHOCK trial = Femoral versus radial approach for primary percutaneous intervention in cardiogenic shock : a subanalysis from the ECLS-SHOCK trial - Abumayyaleh, Mohammad S. A.; Thiele, Holger; Rassaf, Tienush; Mahabadi, Amir Abbas; Lehmann, Ralf; Eitel, Ingo; Skurk, Carsten; Clemmensen, Peter; Hennersdorf, Marcus; Voigt, Ingo; Linke, Axel; Tigges, Eike; et al. (European heart journal - acute cardiovascular care, 2025)
Cardiogenic shock (CS) is a life-threatening complication of acute coronary syndromes. Early revascularization with treating the culprit lesion improves survival. Nevertheless, the impact of access site (femoral vs. radial) on outcomes in infarct-related CS also in conjunction with extracorporeal life support (ECLS) remains unclear.This subanalysis of the ECLS-SHOCK trial included patients with infarct-related CS treated with or without ECLS, divided into femoral and radial access groups. The primary endpoint was 30-day mortality. Secondary endpoints included renal replacement therapy, repeat revascularization, reinfarction, rehospitalization for congestive heart failure, and poor neurological outcome (Cerebral Performance Categories 3-5) within 30 days. Safety outcomes included bleeding and peripheral vascular complications. Among 415 patients, percutaneous coronary intervention was initially intended through femoral (n = 304; 72.9%) or radial (n = 111; 26.6%) access. In the intended access site analysis, 25 patients (22.5%) in the radial group switched to femoral access, while 3 patients (1%) in the femoral group switched to radial access prior to or after coronary angiography. At 30 days, the overall mortality rate was higher in the femoral group compared with the radial group (52.0 vs. 37.8%) with a relative risk (RR) of 1.37, a 95% confidence interval (CI) of 1.06-1.78, and a P-value of 0.011 with no significant differences in the crude rates of secondary and safety endpoints. In the analysis based on the actual access site (as opposed to intended access site used), 7.8% of patients in the ECLS arm switched from radial to femoral, while 7.5% of patients in the conservative arm switched from radial to femoral for or after coronary angiography. Mortality rates were higher in the femoral group for both ECLS arm (52.7 vs. 26.8%; P = 0.003; RR, 1.96; 95% CI, 1.16-3.32) and conservative arm (52.2 vs. 37.5%; P = 0.074; RR, 1.39; 95% CI, 0.94-2.06). In a multivariate analysis, femoral access was associated with a trend for predicting adjusted 30-day mortality (RR, 1.22; 95% CI, 0.95-1.55; P = 0.11).In myocardial infarction-related CS, nearly one-fifth of patients with intended radial access switched to femoral. In multivariate analysis, femoral access was associated with a trend to adversely affect 30-day mortality.